Methodological aspects of assessing the efficiency of regional social policy in overcoming of social orphanhood - V. Babakaev, Sergey (2020)
Among the methodological issues of studying the problem of social orphanhood, an important place is occupied by the search for effective markers for assessing dynamics on the one hand, and the effectiveness of social policy in overcoming social orphanhood on the other. That attempt to systematically evaluate the scale and severity of the phenomenon, as well as the key factors that determine its dynamics. However, these approaches do not allow us to identify the connection between social work and the dynamics of improving the situation with social orphanhood in the region. The presented study proposes a new model for assessing the dynamics of social orphanhood. Its difference from other methodological approaches is that the main emphasis is on assessing the orientation of the complex of shifts in the processes of identifying, placement of orphans and canceling decisions on their transfer to families. This model allows us to assess the role of social policy in overcoming social orphanhood. In this model, we developed authoring methods for ranking the regions of Russia by the dynamics of indicators integrated into the "auspiciousness" index of changes in the social orphanhood. Also, the author presents a model that assesses the situation in the region from the point of view of the "social support efficiency index" to overcome the social orphanhood. The models used to assess the dynamics of social orphanhood have been tested as a tool for identifying key markers of the efficiency of social policy.